(3QSGdI aj GdMOhOs - (3GdMSjf Hf YHO Gddg Hf GdMSf Hf Ydj Hf SjfG , CHh Ydj GdnHrdNqj Ke GdoHNGQqj GdeYQha HGHf SjfG, (B427 (3g`s
(3ChdgG (B:s
(3HYO GdHSedI GeG HYO aEf GUObGFj SCdhfj Cf Cedj Ydjge MOhO CTjGA jWGdHhffj HJMOjOgG aGSJYajJ ef Pdc YdekG HCfg ef GdeYPQ Ydi GdHTQ s
(3BNQgG (B:s
(3hGdbOje HMH GdPGJ agh GdTF GdPj djS dg hLhO PGJg Cfg eHOC Hg hLH aGdbOje HMSH GdReGf s
(3Vef eLehY , JQJjHgG (B: 24s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
Keywords: (3eJaQbGJs